2015
DOI: 10.1021/acs.chemmater.5b02952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 Coating on Stabilizing LiNi0.4Mn0.4Co0.2O2 Cathodes

Abstract: Using atomic layer deposition of Al 2 O 3 coating, improved high-voltage cycling stability has been demonstrated for the layered nickel-manganese-cobalt pseudo-ternary oxide, LiNi 0.4 Mn 0.4 Co 0.2 O 2 . To understand the effect of the Al 2 O 3 coating, electrochemical impedance spectroscopy, operando synchrotron-based X-ray diffraction, and operando X-ray absorption near edge fine structure spectroscopy have been utilized to characterize the structure and chemistry evolution of the LiNi 0.4 Mn 0.4 Co 0.2 O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
130
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(133 citation statements)
references
References 46 publications
2
130
1
Order By: Relevance
“…21,22 Arumugam et al showed the benficial impact of an Al 2 O 3 coating on NMC622 in cells tested to 4.4 V. 23 In all electrolytes tested, cells with the Al 2 O 3 -coated NMC622 had larger coulombic efficiency, lower charge end point capacity slippage and better capacity retention than cells using uncoated NMC622. The impact of two different coatings on NMC622 will be explored in this preliminary work.…”
Section: 12mentioning
confidence: 98%
“…21,22 Arumugam et al showed the benficial impact of an Al 2 O 3 coating on NMC622 in cells tested to 4.4 V. 23 In all electrolytes tested, cells with the Al 2 O 3 -coated NMC622 had larger coulombic efficiency, lower charge end point capacity slippage and better capacity retention than cells using uncoated NMC622. The impact of two different coatings on NMC622 will be explored in this preliminary work.…”
Section: 12mentioning
confidence: 98%
“…These findings lead to the application of coating techniques and other surface treatments to stabilize vulnerable surfaces on the cathode materials. Such coating and surface treatments have been frequently verified as effective methods for improving cathode cycling stability19202122232425262728. Besides chemical instability, another degradation mechanism is associated with the volume change of the material upon lithium (Li) ion extraction and reinsertion.…”
mentioning
confidence: 99%
“…Since B 2 O 3 oxide coating was reported to modify cathode materials for the first time byAmatucci 20 , various coating materials and methods were explored to improve the performance, chemical deposition 35 , magnetron sputtering36 and ALD[22][23] . Although these coating progresses have improved the performance, it is still difficult to ensure the homogeneity of the coating layer and avoid self-nucleation of the coating material.…”
mentioning
confidence: 99%